Assessment of mint (Mentha spp.) species for large-scale production of plantlets by micropropagation (Acta Scientiarum. Biological Sciences, 2015)
Species of the genus Mentha produce essential oils which are widely used in pharmaceutical and cosmetic industries. Current study evaluates the potential for in vitro propagation and estimates mass production of plantlets of Mentha species. Nine species (M. piperita, M. suaveolens, M. canadensis, M. longiflora, M. aquatica, M. arvensis, Mentha x gracilis, M. gracilis and M. spicata) were propagated with five successive 30-day subcultures in MS medium supplemented with NAA (0.05 µM) and BAP (4.4 µM). Shoots were rooted in MS with IBA, IAA or NAA (0.0; 0.25; 0.5; 2.5 or 5.0 µM). The rooted plantlets were finally acclimatized in a greenhouse. Studied species increased in multiplication rates between 4.2 and 9.0-fold per month. M. piperita, M. longiflora, M. arvensis, M. x gracilis and M. gracilis showed the greatest potential for plantlet production since the estimated production varied between 6,000 and 27,000 plantlets after five 30-days subcultures. The addition of auxin to the medium did not influence root induction. However, IAA at a concentration of 5 µM provided the best results for root length and fresh weight, with averages 11.1 cm and 0.16 g, respectively. Survival of plantlets reached 100% during the greenhouse acclimatization process.